2018
DOI: 10.1530/eje-17-0546
|View full text |Cite
|
Sign up to set email alerts
|

Targeting either GH or IGF-I during somatostatin analogue treatment in patients with acromegaly: a randomized multicentre study

Abstract: (1) Discordant values in terms of high GH levels are prevalent in SA patients and more so if applying glucose-suppressed GH; (2) targeting discordant levels of either GH or IGF-I translates into SA dose increase and improved biochemical control; (3) even though QoL was not improved in this study, we suggest biochemical assessment of disease activity to include glucose-suppressed GH also in SA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
15
1
2
Order By: Relevance
“…On the contrary, uncontrolled GH or IGF-1 resulted in a significant increase of the SMR of 1.96 (CI: 1.25-3.05, I2: 78%) as compared with the general population, according to this meta-analysis. Once medically treated, it remains unknown if targeting GH or IGF-1 instead of both parameters in patients with acromegaly could be a suitable strategy, however this question has been recently raised by the group of Dal et al [34]. While somatostatin analogs have been associated either with a higher risk of GH discordance (i.e., IGF-1 normal with unsuppressed GH under OGTT) [22,34,35] or a higher proportion of IGF-1 discordance [21], this study shows that increasing the dose of somatostatin analogs based on either GH or IGF-1, significantly increased the proportion of controlled patients after a follow-up of 12 months.…”
Section: Endocrinementioning
confidence: 99%
“…On the contrary, uncontrolled GH or IGF-1 resulted in a significant increase of the SMR of 1.96 (CI: 1.25-3.05, I2: 78%) as compared with the general population, according to this meta-analysis. Once medically treated, it remains unknown if targeting GH or IGF-1 instead of both parameters in patients with acromegaly could be a suitable strategy, however this question has been recently raised by the group of Dal et al [34]. While somatostatin analogs have been associated either with a higher risk of GH discordance (i.e., IGF-1 normal with unsuppressed GH under OGTT) [22,34,35] or a higher proportion of IGF-1 discordance [21], this study shows that increasing the dose of somatostatin analogs based on either GH or IGF-1, significantly increased the proportion of controlled patients after a follow-up of 12 months.…”
Section: Endocrinementioning
confidence: 99%
“…The authors reported significantly higher GH nadir levels along with worse symptoms and quality of life in controlled patients treated with somatostatin analogues compared to surgery despite comparable IGF-I and fasting GH levels [109]. Dose escalation of somatostatin analogues minimized the discordance between IGF-1 and nadir GH levels with, however, no improvement in quality of life [108]. Furthermore, higher GH nadir levels after an OGTT as well as after mixed meals were observed in patients treated with somatostatin analogues compared to patients successfully treated with surgery and matched to IGF-1 levels suggesting a residual disease activity in somatostatin analogue treated patients despite normalized IGF-I levels [107].…”
Section: Ogtt In the Follow-up Of Acromegalymentioning
confidence: 99%
“…Furthermore, discrepant results from GH nadir and IGF-I analysis can also delay diagnosis, and apart from assay problems, biological variables might be important (8). Sex, BMI and different cycle phase have been shown to influence the GH nadir , but few studies systematically addressed this, and there is no consensus if and how cut-offs should be adjusted to such variables (9,21,22,23,24,25,26,27).…”
Section: Introductionmentioning
confidence: 99%